Formation of Ferric Phosphate Minerals and Adsorption of Phosphate on Amorphous Iron Oxide - Warry, Norman D. (My University, 1972)
A series of experiments was designed to investigate the reaction of orthophosphate with amorphous iron oxide under conditions approximating those encountered in lacustrine environments. A dynamic physical sorption reaction explained the uptake of the ion onto the solid. When total P was <200 μg/l and total Fe≥2.5 mg/l, more than 95% of the dissolved orthophosphate was adsorbed onto the Fe(OH)3 particles. When total Fe was = 0. 25 mg/l or less, no phosphate was adsorbed. The sorption was a maximum in the pH range between 4 and 7.5, as long as particulate Fe(OH)3 was present in the solution. Outside of this pH range, the sorption of phosphate by the solid decreased dramatically. The lower limit of Eh stability for the P-Fe(OH)3 complex was found to be on the order of 200 mv, equivalent to 1 mg/l D. O. Below this Eh value, the complex dissolved. No upper limit of Eh stability was found.
The complex was capable of being altered to a crystalline mineralogical phase if total orthophosphate was increased to > 10^-4M. The structure of this phase was quite similar to that expected for a mixture of the ferric phosphate minerals strengite and metastrengite. (ΣHPO4^-3 ≃1x10^-3M, Eh > 300 mv, pH≃7) of this solid with those necessary for the formation of strengite (Nriagu, 1972b) show a good correlation. Formation of these mineral phases in lacustrine sediments is not likely, however, because the requisite conditions are rarely satisfied in natural sedimentary environments.
Title: Formation of Ferric Phosphate Minerals and Adsorption of Phosphate on Amorphous Iron Oxide, Author: Norman D. Warry, Location: Thode